Impact of winter holiday and government responses on mortality in Europe during the first wave of the COVID-19 pandemic. (24th February 2021) - Björk, Jonas; Mattisson, Kristoffer; Ahlbom, Anders
Abstract: Background: This aggregated population study investigated the impact of the seemingly quasi-randomly assigned school winter holiday in weeks 6–10 (February to early March) on excess mortality in 219 European regions (11 countries) during the COVID-19 pandemic in the spring 2020. A secondary aim was to evaluate the impact of government responses to the early inflow of infected cases. Methods: Data on government responses weeks 8–14 were obtained from the Oxford COVID-19 Government Response Tracker. Regional data on total all-cause mortality during weeks 14–23 in 2020 were retrieved from Eurostat and national statistical agencies and compared with the average mortality during same period 2015–2019. Variance-weighted least square regression was used with mortality difference as dependent variable with adjustment for country, population density and age distribution. Results: Being a region with winter holiday exclusively in week 9 was in the adjusted analysis associated with 16 weekly excess deaths [95% confidence interval (CI) 13–20] per million inhabitants during weeks 14–23, which corresponds to 38% of the excess mortality in these regions. A more stringent response implemented in week 11, corresponding to 10 additional units on the 0–100 ordinal scale, was associated with 20 fewer weekly deaths (95% CI 18–22) per million inhabitants. Conclusions: Winter holiday in week 9 was an amplifying event that contributed importantly to the excess mortality observed in the study regions during the spring 2020. Timely government responses to the resulting early inflow of cases reduced the excess in mortality.